Growing Apart: A Longitudinal Assessment of the Relation Between Post-traumatic Growth and Loneliness Among Combat Veterans - Stein, Jacob Y.; Levin, Yafit; Bachem, Rahel; Solomon, Zahava (Frontiers in Psychology, 2018)
The aftermath of war-related trauma may entail psychological devastation that is ‎typically accompanied by various deleterious phenomena. These include, but not limited to, ‎high rates of loneliness. However, trauma may also result in positive outcomes such as ‎personal, spiritual, and relational prosperity, typically considered under the conceptual ‎framework of posttraumatic growth (PTG). PTG may theoretically contribute to either ‎loneliness amelioration (e.g., via increasing one's appreciation of close relationships) or ‎exacerbation (e.g., by increasing one's sense of undergoing experiences that others do not ‎share). Loneliness, on the other hand, may potentially hinder PTG by fostering negative social ‎cognitions and behaviors, or otherwise lead to personal growth. The relations between the two ‎phenomena, however, have yet to be investigated. Filling this gap, the current study examined ‎the aforementioned potentialities by utilizing an autoregressive cross-lagged modeling ‎strategy (ARCL) with a cohort of 260 Israeli combat veterans assessed 30, 35 and 42 years ‎after their participation in the 1973 Yom Kippur War. Results indicated that higher rates of ‎PTG were consistently related to higher rates of loneliness both cross-sectionally and ‎longitudinally. Loneliness, however, did not longitudinally predict PTG rates. It is suggested ‎that these findings may be understood in light of the observation that veterans' loneliness is ‎primarily related to the experience of being experientially out of sync with people who have ‎not endured war experiences. It is suggested that this experiential loneliness may include not ‎only the negative but also the positive ramifications of undergoing such traumas (i.e., PTG). ‎We, therefore, argue that while PTG may include authentic positive transformations it may ‎also lead to more negative ramifications, and these should be identified and addressed by ‎researchers and clinicians alike. Thus, as study limitations are acknowledged, clinical ‎implications and future research directions are suggested.‎